Modelos para el análisis documental de la fotografía - Torregrosa Carmona, Juan Francisco (Documentación de las Ciencias de la Información, 2010)
In this article the documentary analysis of the photography is approached, especially that of press, from the point of view of the models established by the most relevant authors in the matter. To offer a suitable context, there are revised the principal characteristics inherent in the photojournalistic document. With the mention of its most excellent evolutionary steps inside our environment and some unavoidable references at the moment of investigating in this question, one will try to demonstrate that the academic area grants today the importance and justification of the scientific interest towards the photography that during decades one denied to it.
Keywords: Documentation; Photography; Documentary analysis; Press